Coaxial Filters Optimization Using Tuning Space Mapping in CST Studio - Wolansky, David; Tkadlec, Roman (Společnost pro radioelektronické inženýrství, 2011)
This paper deals with the optimization of coaxial filters using Tuning Space Mapping (TSM) method implemented to CST environment. The function of fine and coarse model and their link between each other is explained. In addition, supporting macros programmed in VBA language, which are used for maximum efficiency of the optimization from the user´s point of view, are mentioned. Macros are programmed in CST and are also used for automatic calibration constants determination and for automatic calibration process between the coarse model and the fine model. The whole algorithm is illustrated on the particular seven-order filter design and optimized results are compared to measured ones.
Keywords: Tuning Space Mapping; optimization; fine model; coarse model; VBA language; CST